Administrators’ Role in Managing Changes in Institutions of Higher Learning / YBhg. Tan Sri Dato’ Seri Arshad Ayub - Ayub, Arshad (2010)
Leadership can be anything from monitoring an elementary school class, a fine battlefield commander to a bold CEO of a floundering company to a prime minister or president who has to take his country out of an economic recession. Leadership can occur at just about any age, and it is much more than simply wielding power. Great leaders are not merely born; many of them develop their leadership styles through study, trial, and error, and the experience of success. Great leaders are as concerned about others as they are with themselves, and they are always concerned with the change and growth of the organization and the people around them.